Correlation between gluteus muscle activity and dynamic control of the knee joint in a single-leg landing task in badminton - Hu, Z.; Kim, Y.; Dong, T.; Meng, X.; Dong, M.; Kim, S. (International Journal of Performance Analysis in Sport, 2023)
The purpose of this study was to explore the relationship between gluteal muscle activity patterns and dynamic control of the knee joint during a high-risk single-leg landing task in badminton. Thirty-four badminton players perform a single-leg landing test after a backhand side overhead stroke. This test collected lower limb kinematics, ground reaction force, and gluteus muscle activity data using a marker-based motion capture system, force plates, and electromyography(EMG). The relationship between gluteus maximus(GMAX), gluteus medius(GMED), and knee flexion angle, valgus angle, extension moment, valgus moment, and tibial anterior shear force was analysed by Pearson`s correlation coefficient. The results show that Peak knee valgus was strongly and moderately positively correlated with the activity of the gluteus maximus(GMAX) and gluteus medius(GMED) muscles. Peak proximal tibial shear force was moderately positively correlated with gluteus maximus and gluteus medius activation. Our findings suggest a correlation between the gluteus muscles and the dynamic control of the knee joint during the impact phase of the single-leg landing task in badminton. Optimising neuromuscular control of the glutes may be beneficial in reducing the risk of Anterior Cruciate Ligament(ACL) injury in badminton players during single-leg landing tasks.